2016
DOI: 10.1002/ajp.22555
|View full text |Cite
|
Sign up to set email alerts
|

Host age, social group, and habitat type influence the gut microbiota of wild ring‐tailed lemurs (Lemur catta)

Abstract: The gut microbiota contributes to host health by maintaining homeostasis, increasing digestive efficiency, and facilitating the development of the immune system. The composition of the gut microbiota can change dramatically within and between individuals of a species as a result of diet, age, or habitat. Therefore, understanding the factors determining gut microbiota diversity and composition can contribute to our knowledge of host ecology as well as to conservation efforts. Here we use high-throughput sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
108
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(134 citation statements)
references
References 56 publications
11
108
3
Order By: Relevance
“…Bacterial diversity was higher in wild individuals and lower for individuals living in captivity. These findings are congruent with previous evidence, which has demonstrated that perturbed habitat as well as captivity conditions act as stressors and are correlated with decreased gut microbial diversity (Amato et al, 2013; Barelli et al, 2015; Bennett et al, 2016). The difference in similarity patterns observed for wild and captive individuals could be explained by changes in diet.…”
Section: Discussionsupporting
confidence: 92%
“…Bacterial diversity was higher in wild individuals and lower for individuals living in captivity. These findings are congruent with previous evidence, which has demonstrated that perturbed habitat as well as captivity conditions act as stressors and are correlated with decreased gut microbial diversity (Amato et al, 2013; Barelli et al, 2015; Bennett et al, 2016). The difference in similarity patterns observed for wild and captive individuals could be explained by changes in diet.…”
Section: Discussionsupporting
confidence: 92%
“…However, studies on wild mammals investigating sex and age class differences in microbiota composition have generally reported low effect sizes (Amato et al., 2014; Bennett et al., 2016; Tung et al., 2015). Large sample sizes may be needed to detect these effects, if they exist, which may explain why we found statistically significant effects in the model combining all samples, but not in the monthly data subsets.…”
Section: Discussionmentioning
confidence: 99%
“…The metazoan gut is colonized by an opportunistic and commensal microbiota that is shaped by a combination of exogenous (diet and habitat) and endogenous (gut environment and host genetics) factors (Bennett et al., ; Bolnick, Snowberg, Hirsch, Lauber, Knight, et al., ; Bolnick, Snowberg, Hirsch, Lauber, Org, et al., ; Daniel et al., ; David et al., ; Dehler, Secombes, & Martin, ; Muegge et al., ; Pérez‐Cobas et al., ; Yun et al., ). It has been suggested that different factors act on different aspects of gut microbial community composition (Zhao et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Pronounced interpopulation and interindividual variations in the gut microbial communities are observed in many species, with contributions from endogenous factors, such as age, sex and genotype, and exogenous factors, including habitat and diet (Bennett et al, 2016;Han, Lee, Jeong, Jeon, & Hyun, 2017;Kovacs et al, 2011). As gut microbes can help in the digestion of ingested food, changes in gut microbial populations could entail a shift in the genes that carry out metabolic reactions in the gastrointestinal tract, which could impact the food utilization efficiency of the host (Holm et al, 2016;Turnbaugh et al, 2006).…”
mentioning
confidence: 99%